2010
DOI: 10.1088/0264-9381/27/24/245007
|View full text |Cite
|
Sign up to set email alerts
|

Statistical constraints on binary black hole inspiral dynamics

Abstract: We perform a statistical analysis of the binary black hole problem in the post-Newtonian approximation by systematically sampling and evolving the parameter space of initial configurations for quasi-circular inspirals. Through a principal component analysis of spin and orbital angular momentum variables we systematically look for uncorrelated quantities and find three of them which are highly conserved in a statistical sense, both as functions of time and with respect to variations in initial spin orientations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…While the work presented here is limited to the nonprecessing case, our results provide the first hints, together with [24] for precessing inspiral dynamics (see also [12]), [22] for quasi-normal mode ringing, and studies using a Singular Value Decomposition (SVD) technique [23,34,35] that a full representation of the eightparameter space of inspiral-merger-ringdown waveforms (either numerical, Effective-One-Body, or phenomenological ones) might actually be achievable with a relatively compact reduced basis. If this is the case, then there is hope that the number of simulations needed to represent the space of precessing binary inspirals might be relatively small (perhaps, on the order of several thousand for advanced LIGO but not orders of magnitude larger than this), thus allowing for a tractable number of numerical simulations if the parameters are chosen with malice of forethought from our reduced basis studies.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…While the work presented here is limited to the nonprecessing case, our results provide the first hints, together with [24] for precessing inspiral dynamics (see also [12]), [22] for quasi-normal mode ringing, and studies using a Singular Value Decomposition (SVD) technique [23,34,35] that a full representation of the eightparameter space of inspiral-merger-ringdown waveforms (either numerical, Effective-One-Body, or phenomenological ones) might actually be achievable with a relatively compact reduced basis. If this is the case, then there is hope that the number of simulations needed to represent the space of precessing binary inspirals might be relatively small (perhaps, on the order of several thousand for advanced LIGO but not orders of magnitude larger than this), thus allowing for a tractable number of numerical simulations if the parameters are chosen with malice of forethought from our reduced basis studies.…”
Section: Discussionsupporting
confidence: 54%
“…For the non-precessing inspiral waveforms, we find a very moderate increase in the number of RB elements as the dimensionality of the parameter space is increased from 2D to 4D. While this number could and might change significantly for precessing binaries, former results in [24] show dimensionality reduction in the precessing case (with respect to the spin dynamics).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…While we may assume that η and | S i | remain essentially constant throughout inspiral and merger, the spin directions generally evolve, so a useful parameterization of the system should take care to distinguish components of the spin-direction space with physically distinct effects on the waveforms [11].…”
mentioning
confidence: 99%
“…Work over the last few years has shown that gravitational waveforms exhibit redundancy in the parameter space [37][38][39][40][41][42], suggesting that the amount of information necessary to represent a fiducial waveform model is smaller than might be anticipated. This reduction can be captured accurately using only a remarkably few number m of representative waveforms.…”
Section: Introductionmentioning
confidence: 99%